Early mobilisation after total hip or knee arthroplasty: A multicentre prospective observational study - Chua, Matthew J. (PLoS One, 2017)
OBJECTIVE: Early mobilisation is recommended following total hip arthroplasty (THA) or total knee arthroplasty (TKA) to prevent venous thromboembolism (VTE). We sought to determine the proportions of patients that first mobilised on post-operative day 0 (POD 0) and factors associated with earlier time to mobilisation. METHODS: A prospective cohort study was conducted involving patients with hip or knee osteoarthritis who had undergone primary unilateral THA (n = 818) and TKA (n = 989) at 19 Australian hospitals. Patient-related (e.g. age, gender, body mass index), treatment-related (e.g. hospital site, presence of indwelling catheter) and mobilisation-related variables were collected on standardised forms. Time was measured by post-operative days, where POD 0 was defined as the day of surgery ending at midnight. Multivariate Poisson regression analysis identified associations between patient- and treatment-related covariates and time to mobilisation. RESULTS: Inter-hospital variation was evident, but overall, only 9.4% of THA and 5.6% of TKA patients mobilised on POD 0. For THA patients, earlier time to mobilisation was associated with hospital site and absences of an indwelling catheter and acute complications. For TKA patients, earlier time to mobilisation was associated with hospital site and absence of donor blood transfusion. CONCLUSIONS: Few THA and TKA patients mobilise POD 0, although some hospitals appear more aggressive with their mobilisation attempts than others. Treatment-related factors, not patient-related, are associated with post-operative day of mobilisation, indicating the potentially pivotal role of service providers in promoting early mobilisation to improve health outcomes and reduce rates of VTE.